Helping orphans to help themselves - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
The NGO Help to Self Help is assisting under-privileged children, orphans and rural communities to learn productive skills and achieve better food production. This interview features two staff from the organisation based in Arusha, Tanzania